The Effect of the PBL Learning Model using Videos to Improve Student Motivation and Learning Outcomes in Geopolitical Material in Timor-Leste - Genito Ferandes Xavier; Sugeng Utaya; Sumarmi Sumarmi (FKIP - Universitas Riau, 2026)
Low student motivation and poor learning outcomes in geopolitics materials are often associated with the dominance of lecture-based methods and the limited use of instructional media. This study aims to determine the effect of the Problem-Based Learning (PBL) model assisted by video on students’ motivation and geography learning outcomes. The research was conducted at Ensino Secundario Geral Catholic St. Madalena de Canossa, Dili, Timor-Leste, using a quasi-experimental method with a non-equivalent control group design. The subjects were Grade X students selected through purposive sampling based on comparable academic abilities. Data were collected through learning outcome tests and motivation questionnaires and analyzed using the t-test. The results showed that the average learning outcome score in the experimental class increased from 62.3 to 85.5, while the control class improved from 57.3 to 72.0. Statistical analysis indicated a significant effect of the video-assisted PBL model on students’ motivation and learning outcomes. In conclusion, the implementation of video-assisted PBL is more effective than conventional teaching methods in enhancing students’ motivation and geography learning outcomes in geopolitics materials.